Measurement of tumor necrosis factor-alpha, interleukin-6, Fas ligand, interleukin-1α, and interleukin-1β in the aqueous humor of patients with open angle glaucoma using multiplex bead analysis - Borkenstein, Andreas; Faschinger, Christoph; Maier, Richard; Weger, Martin; Theisl, Anna; Demel, Ulrike; Graninger, Winfried; Irene, Holzer; Mossböck, Georg (Molecular vision, 2013)
Various cytokines, including tumor necrosis factor-alpha (TNF-α), Fas ligand (FasL), interleukin-1α (IL-1α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), contribute to the pathogenesis of primary open angle glaucoma (POAG). The present study was set to measure these cytokines in the aqueous humor of patients with POAG and in control subjects using multiplex bead analysis. Twenty-five patients with POAG and 29 control subjects were enrolled in this case-control study. Aqueous humor concentrations of the cytokines (IL-1 α, IL-1 β, IL-6, FasL, and TNF- α) were measured using multiplex bead analysis. Mean aqueous humor levels of IL-6 were significantly lower in patients with POAG compared to the control subjects (9.3±23.7 versus 55.3±94.4 pg/ml; p=0.002). No significant difference in the aqueous humor concentration of IL-1β was found between patients with POAG and control subjects (0.5±0.8 versus 0.4±0.8 pg/ml; p=0.85.) Concentrations of IL-1α, TNF-α, and FasL were below limits of detection. No significant correlation was found between IL-6 concentration and age, duration of disease, cup/disc ratio, or mean deviation. In the present study, we found significantly lower concentrations of IL-6 in the aqueous humor of patients with POAG.